No detectable impact of chronic oral lactic acid exposure on honey bee health: Insights from survival, lactate accumulation and head transcriptome - Caroline Vilarem; Vincent Piou; Lucie Bouly; Frédéric Julien; Rachel Fourdin; Nathalie Vialaneix; Matthias Zytnicki; Angélique Vétillard (Ecotoxicology and Environmental Safety)
Natural acids such as oxalic, formic or lactic acids are used as alternative treatments against Varroa destructor, the parasitic mite of honey bees (Apis mellifera). Lactic acid has recently been shown to impair mites’ grip skills through local action after exposure of adult honey bees. However, little is known about the lethal and sublethal effects of lactic acid on honey bees. In this work, we investigated the effects of chronic oral exposure to lactic acid through a contaminated diet on age-controlled worker bees. We monitored survival under artificial conditions, quantified lactate levels in various worker organs (the digestive tract, the thorax, the fat body, the head and the haemolymph) and analysed the transcriptome of the workers’ heads. Our results indicate that consuming lactic acid at residual concentration (1.5 mg/mL) did not impact the survival. No lactate accumulation was detected in any of the honey bee organs analysed. Furthermore, transcriptomic analysis on the bees’ heads revealed no differences in gene expression. While further research on sublethal effects is still needed, this work provides one of the first reports on the off-target effects of lactic acid on honey bee health.